Pembangunan Aplikasi Penjualan Hasil Panen Kelompok Tani untuk Konsumen Berbasis Android dengan Metode Prototyping (Studi Kasus: Kelompok Tani Langgeng Mandiri) - I Made Resza Surya Adinata; Herman Tolle; Adam Hendra Brata (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Farmers are the biggest economic contributors in Indonesia. However, the income from farming is still considered very low resulting in farmers becoming less prosperous. One of the ways to increase their income is to utilize new ways to generate income for farmers in the form of broadening their market. This research was done with the Langgeng Mandiri Farmer Group who were connected with household customers or restaurants in the Malang City region. Based on the business model done on the Langgeng Mandiri Farmer Group, resulted in a solution in the form of a mobile application that can bridge the farmer group with consumers in terms of sales of crops. The development of this application uses a prototyping method. Requirements of the users are formed into a mockup and evaluation is done using a query evaluation technique which will result in two iterations. Implementation of the application is built on an Android base and data communication with a database serves was done through the assistance of a web service. The operating of the application during the testing phase were done with expected results based on requirement scenario, the application was able to run on android version 5.0 (Lolipop) to android version 9.0 (Pie) and the application was well-received by the farmer group and the consumers.